2020
DOI: 10.3389/fevo.2020.501502
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Climate and Management on Patterns of Taxonomic and Functional Diversity of Recreational Park Vegetation

Abstract: Recreational urban parks support diverse assemblages of plants that through their functions, contribute beneficial services to billions of individuals throughout the world. Drivers of vegetation-derived services in parks are complex, as climate and park management interact with the functioning of multiple species of vegetation types. Yet, informal observations suggest that recreational parks are constructed consistently to specific principles of landscape design. Here we ask: what are the patterns of functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 78 publications
4
4
0
Order By: Relevance
“…While urban tree community composition does not exhibit convergence (Jenerette et al, 2016), other components of urban ecosystems do, including climate (Hall et al, 2016), land management (Polsky et al, 2014), and soils (Trammell et al, 2020). Convergence in urban tree carbon sequestration is consistent with a previous finding of convergent urban vegetation functional distributions across climate gradients through changes in species selection (Ibsen et al, 2020).…”
Section: Reported Rates Of Urban Tree Productivitysupporting
confidence: 85%
“…While urban tree community composition does not exhibit convergence (Jenerette et al, 2016), other components of urban ecosystems do, including climate (Hall et al, 2016), land management (Polsky et al, 2014), and soils (Trammell et al, 2020). Convergence in urban tree carbon sequestration is consistent with a previous finding of convergent urban vegetation functional distributions across climate gradients through changes in species selection (Ibsen et al, 2020).…”
Section: Reported Rates Of Urban Tree Productivitysupporting
confidence: 85%
“…These results occurred even for tree species that never naturally experience the extreme heat and arid conditions found in the desert. The combination of irrigation and extreme climates in arid urban cities shows how human facilitation and trait flexibilities create novel functional compositions, as increased functional plasticity opens up the arid urban species pool to greater diversity [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that each green space's property is separate, owing to different management practices and surroundings. This difference affects the expression of plant functional traits [29][30][31]. The types of urban green space are different due to geography, socioeconomics, environment, and function [4].…”
Section: Introductionmentioning
confidence: 99%